Interdependence of Thyroid and Corticosteroid Signaling in Vertebrate Developmental Transitions - Rousseau, Karine; Dufour, Sylvie; Sachs, Laurent M. (Frontiers in Ecology and Evolution, 2021)
Post-embryonic acute developmental processes mainly allow the transition from one life stage in a specific ecological niche to the next life stage in a different ecological niche. Metamorphosis, an emblematic type of these post-embryonic developmental processes, has occurred repeatedly and independently in various phylogenetic groups throughout metazoan evolution, such as in cnidarian, insects, molluscs, tunicates or vertebrates. This review will focus on metamorphoses and developmental transitions in vertebrates, including typical larval metamorphosis in anuran amphibians, larval and secondary metamorphoses in teleost fishes, egg hatching in sauropsids and birth in mammals. Two neuroendocrine axes, the hypothalamic-pituitary-thyroid and the hypothalamic-pituitary-adrenal/interrenal axes, are central players in the regulation of these life transitions. The review will address the molecular and functional evolution of these axes and their interactions. Mechanisms of integration of internal and environmental cues, and activation of these neuroendocrine axes represent key questions in an “eco-evo-devo” perspective of metamorphosis. The roles played by developmental transitions in the innovation, adaptation, and plasticity of life cycles throughout vertebrates will be discussed. In the current context of global climate change and habitat destruction, the review will also address the impact of environmental factors, such as global warming and endocrine disruptors on hypothalamic-pituitary-thyroid and hypothalamic-pituitary-adrenal/interrenal axes, and regulation of developmental transitions.